2018
DOI: 10.15695/jstem/v1i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Demonstrating the Efficacy of the Health Sciences and Technology Academy: Using Archival Standardized Test Scores to Analyze an OST College-Preparatory Program for Underserved Youth

Abstract: To combat educational and health disparities, out-of-school-time (OST) STEM enrichment programs provide services to underserved youth to encourage them to pursue college and health careers. This article describes a study conducted to determine if the Health Sciences and Technology Academy (HSTA) program participants who receive year-round educational interventions to prepare them for STEM and health sciences majors performed better on the West Virginia Educational Standards Test (WESTEST2) than non-participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One might argue that there is a selection bias into the program, which brings into question the validity of this study. We acknowledge that there is a possibility of selection bias; however, this study provides a controlled evaluation (Winkleby et al, 2013) on a matched cohort study of HSTA and non-HSTA high school participants to determine if the outcomes are program versus selection effect (Smith-Branch et al, 2018). In the past several years, randomized controlled trials (RCTs) have become increasingly popular in the education field (Connolly et al, 2018;Deaton and Cartwright, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One might argue that there is a selection bias into the program, which brings into question the validity of this study. We acknowledge that there is a possibility of selection bias; however, this study provides a controlled evaluation (Winkleby et al, 2013) on a matched cohort study of HSTA and non-HSTA high school participants to determine if the outcomes are program versus selection effect (Smith-Branch et al, 2018). In the past several years, randomized controlled trials (RCTs) have become increasingly popular in the education field (Connolly et al, 2018;Deaton and Cartwright, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study is to determine if students who receive the HSTA intervention are more likely to attain higher college entrance standardized test scores and CGPAs because they receive pre-college services that provide them with the foundation to reach their academic potential. In a previous study, HSTA's high school students showed a competitive edge in performance over their Non-HSTA counterparts on state-mandated standardized tests (Smith-Branch et al, 2018). Essentially, HSTA makes a difference in the lives of students in both the development of their skills and knowledge as well as their access to higher education (McKendall et al, 2014).…”
Section: Entry Requirementsmentioning
confidence: 96%
See 1 more Smart Citation
“…In each of the three key program elements described above, participants are exposed to models and connected to mentors, improving retention (Castleman and Page, 2015; Chan et al, 2019;McKendall et al, 2014;Patel et al, 2015;Smith-Branch et al, 2018;Tierney and Garcia, 2014;Wrensford et al, 2019). The HSTA family is a broad and deep support network that includes teachers, administrative staff, near-peer college students, community members, university faculty and staff, students' families, and the HSTA students themselves.…”
Section: Mentoring and Modelingmentioning
confidence: 99%
“…This article described positive outcomes associated with the program. Since then, numerous studies have highlighted the program's success over two decades, including HSTA students exhibiting higher performance in college (McKendall et al, 2019), greater persistence in college (McKendall et al, 2000), greater persistence in STEM majors (McKendall et al, 2000), higher standardized test scores in high school (Smith-Branch et al, 2018), increasing recruitment of underserved students into the STEM workforce (Griffith, 2019;McKendall et al, 2014), and increasing health literacy and healthy behaviors among participants and their families (Chester et al, 2018).…”
Section: Key Strategies 4-7: the Skills Building Rsmentioning
confidence: 99%